Interpretasi Musik Barok Pada Lagu The Trumpet Shall Shound Karya Handel - Taryadi, Taryadi; Latif, Bakhrudin (Institut Seni Indonesia Yogyakarta, 2022)
The reason behind the research of Baroque era music interpretation analysis in The Trumpet Shall Sound by Handel is there are many trumpet players and music students who do not have deep understanding in interpreting the baroque era music correctly. The purpose of this research is to find out the music form and music structure from The Trumpet Shall Sound Song by Handel, also to find out the interpretation of trumpet music instrument in The Trumpet Shall Sound Song by Handel. The method used in this research is qualitative method research since there are no use of numbers as its data source. The research object is focused on the interpretation of the song itself by applying some theories i.e., music form, music structure, the rules of music interpretation of baroque era and the music expression of Baroque era. The data collection was done by observation, interview, and documentation. The analysis is from the interpretation which is analyzed through music interpretation rules of Baroque era which is expected to have an outcome by playing The Trumpet Shall Sound song by Handel with correct music interpretation of Baroque era.